Differences Between Sexual and Nonsexual Homicides of Women in the United States: Findings From the National Violent Death Reporting System - De Veauuse Brown, Natasha F. (Journal of interpersonal violence, 2022)
Sexual homicide (SH) is the most severe outcome of sexual violence and disproportionately affects women. While SH is rare (<1% in the U.S.) and gravely understudied, it is among the most violent, feared, and well publicized forms of murder. Thus, examining predictors is pertinent to identifying targets for prevention and response efforts. Secondary analysis of 2015?2018 National Violent Death Reporting System data on 6461 female homicide victims age 20?64 was conducted to determine if SH represents a unique killing characterized by specific offender, victim, and incident profiles. Law enforcement and coroner/medical examiner narratives were reviewed to identify cases with sexual elements (N=324). Logistic regression estimated odds ratios with 95% confidence intervals. Findings highlight important differences between SH and non-SH. SH victims were more likely to be single (AOR=1.7,p=.006), have a substance abuse problem (AOR=1.4,p=.04), or engaged in prostitution (AOR=10.4,p<.001). SH suspects were more likely to be male (AOR=2.5,p=.04), use an illicit substance in the preceding hours (AOR=1.6,p=.03), or had recent contact with police (AOR=1.6,p=.01). SH was more likely to occur in a hotel/motel (AOR=3.0,p=.002), by asphyxiation (AOR =13.38,p<.001), be perpetrated against an acquaintance (AOR=1.64,p=.007), or be precipitated by another serious crime (AOR=2.1,p<.001). Findings advance our understanding of SH victim, suspect, and incident profiles, which can help to better inform police/investigative practices and crime prevention strategies/interventions as well as to improve how SH cases are managed in correctional programs for offenders who have the opportunity for release back into society.